A measure of redenomination risk - Roberto A. De Santis (European Central Bank (ECB), 2015)
Euro redenomination risk is the risk that a euro asset will be redenominated into a devalued legacy currency. We propose a time-varying, country-specific market perception of intra-euro area redenomination risk measure, defined as the quanto CDS of a member country relative to the quanto CDS of a benchmark member country. Focusing on Italy, Spain and France and using Germany as benchmark, we show that the redenomination risk shocks, defined as the unexplained component of the market perception of redenomination risk orthogonal to exchange rate, global, regional and liquidity risks, significantly affect sovereign yield spreads, with Italy and Spain being the countries most adversely affected, followed by France. Finally, foreign redenomination risk shocks spill over and above local redenomination risk shocks, corroborating the fact that this risk is systemic.
Keywords: C32; F36; G12; G15; 330; euro; redenomination risk; sovereign credit spreads; systemic risk